Feasibility Study of Reusing Tarp Banners in the Furniture Production (Sustainability in Debate, 2017)
Vinyl tarp is a low-budget material with good print quality, being widely used for making banners foradvertising campaigns and academic events. In both applications, it quickly turns into waste. In thiscontext, a research project was designed with the objective of studying the feasibility of reusing tarpbanners in the furniture production. The project was developed with students of the Technical Coursein Furniture of the Federal Institute Farroupilha (IFFar), Santa Rosa Campus. In the first stage, tests oncutting, joining, finishing and deforming were performed. The cutting of the material was consideredfeasible. The bonding with adhesives was unsatisfactory, with best results with mechanical bondingwith metallic clips. Regarding the finish, paints were not able to cover homogeneously the surface. Asfor the resistance, the vinyl tarp underwent plastic deformation with the application of localized load.With restrictions, use of the material for production of furniture was considered viable. In the secondstage, the design and prototype of column luminaires, coffee tables, folding benches and stackableniches were developed. The design of products prioritized the reuse and rational use of raw materials, asimplified production process and a contemporary aesthetic, consistent with the precepts of Ecodesignand economic viability.